POLA ASUH ANAK DALAM SERAT PALIATMA - Nurhidayati, Nurhidayati (LITERA, 2005)
This research study is intended to describe child-rearing patterns in Serat Paliatma by KGPAA Mangkunagara IV. The source of the data was Serat Paliatma, consisting 18 stanzas in pupuh Dhandhanggula (the Dhandhanggula song). The data were collected by means of orthographic transliteration, translation, paraphrase, and careful reading and rereading. The data were analyzed descriptively. The data validity was assessed through semantic validity. The data reliability was assessed through reproducibility. The research findings show that there are two child-rearing patterns in Serat Paliatma, namely (1) the one related to religious norms, and (2) the one related to values in life. The former includes acceptance to what is given, gratefulness, and devotion. Meanwhile, the latter covers asceticism, affection, unity, obedience, loyalty to the country, and responsibility. Key words: child-rearing pattern, serat, pupuh